Substantiating the method of filling the goaf using the rock jam phenomenon; Известия вузов. Горный журнал; № 1 - Golik V. I. Vladimir Ivanovich; Valiev N. G. O. Niyaz Gadym Ogly; Razorenov Yu. I. Yury Ivanovich; Lukyanov V. G. Viktor Grigoryevich; Maslennikov S. A. Stanislav Aleksandrovich (2020, 2020)
Заглавие с экрана